Krisen i eurozonen: historien om en forudsigelig krise – der kunne have været undgået - Plaschke, Henrik (Politik, 2013)
The crisis in the Eurozone is part of a general structural crisis with both global and regional dimensions. e US generated nancial crisis was imported into the Eurozone due to the structural weaknesses and accumu- lated tensions built up during the years following the introduction of the common currency. ese tensions express themselves in an accumulation of private debts and in huge balance-of-payments imbalances within the Eurozone. e sovereign debt crisis is the result of these weaknesses and tensions rather than their cause. By insisting on reductions on public spending as a general strategy for the Eurozone economic policies have aggravated not only the situation of the South European periphery of the Eurozone but increasingly also its Northern core. However, the Eurozone is unlikely to break up – rather we are heading for a period of mud- dling through characterized by growing inequalities, social and political tensions and stagnating economic growth.